Efecto de la etapa de levante sobre la producción y reproducción en codornices japónicas (Coturnix coturnix japonica) de postura. - Trillo-Zárate, Z. (2021)
The aim of this study was to evaluate the productive performance of laying quails (Coturnix coturnix japonica). The study was carried out at the poultry farm of the La Molina National Agrarian University in Lima, Peru. In total, 1296 quail distributed in 96 females and 48 males of three ages (45, 52 and 59 days) with 130, 140 and 150 g of body weight, respectively, at the beginning of the laying were used. A random block design witha32 factorial arrangement was used, taking as factors age and weight at the beginning of laying and as a block the weeks of laying (8, 11 and 17). The highest egg mass (10.72 ± 0.41 g/day/bird) was obtained when the quails started laying with 150 g of live weight.